Securitization Revisited Contemporary Applications and Insights (Taylor & Francis, 2019)
This book seeks to interrogate how contemporary policy issues become 'securitized' and, furthermore, what the implications of this process are. A generation after the introduction of the concept of securitization to the security studies field, this book engages with how securitization and desecuritization 'works' within and across a wide range of security domains including terrorism and counter-terrorism, climate change, sexual and gender-based violence, inter-state and intra-state conflict, identity, and memory in various geographic and social contexts. Blending theory and application, the contributors to this volume - drawn from different disciplinary, ontological, and geographic 'spaces' - orient their investigations around three common analytical objectives: revealing deficiencies in and through application(s) of securitization; considering securitization through speech-acts and discourse as well as other mechanisms; and exposing latent orthodoxies embedded in securitization research. The volume demonstrates the dynamic and elastic quality of securitization and desecuritization as concepts that bear explanatory fruit when applied across a wide range of security issues, actors, and audiences. It also reveals the deficiencies in restricting securitization research to an overly narrow set of issues, actors, and mechanisms.$1!# (BThis volume will be of great interest to scholars of critical security studies, international security, and International Relations. Chapter 6 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license https://www.routledge.com/Securitization-Revisited-Contemporary-Applications-and-Insights/Butler/p/book/9780367150372s
English
Keywords: International relations; Military history; Political control and freedoms; Warfare and defence; empirical applications; Climate Change; Conflict Management; Copenhagen School; constructivism; desecuritization; gender-based violence; inter-state conflict; processes; securitization; securitization applications; terrorism